Valoración del dolor en pacientes intubados en la unidad de cuidados intensivos - Quinatoa Quinatoa, Jessica Thalía (2025)
Pain is an unpleasant sensory and emotional experience present in critically ill patients, it can be acute or chronic, and its assessment is still a frequent problem due to its poor recognition and poor treatment, especially in intubated patients under mechanical ventilation and sedation. Pain in these non-communicative patients is moderate to severe due to several factors such as: their ethology, invasive procedures and nursing care; such assessment is complicated by the fact that they cannot communicate their discomfort. For this reason, the objective of this article was to describe the benefits of pain assessment scales used in intubated patients in the Intensive Care Unit, through a qualitative and transversal research by means of bibliographic reviews of scientific articles published in the last five years in different databases, the main results focused on establishing the importance of systematic and protocolized pain assessment in Intensive Care Units, in addition to the description of the most commonly used behavioral scales in non-communicative patients, the behavioral and physiological changes related to the presence of pain during the performance of various nursing procedures (bathing, change of position, aspiration of secretions, etc.) and the degree of sensitivity of the different nursing procedures (bathing, change of position, etc.). ) and degree of sensitivity of the different behavioral pain scales, it was possible to conclude that the nursing staff should have updated knowledge to perform an adequate assessment of the scales and thus provide quality care to these patients.